Jainal Sosialisasi Dan Pendampingan Pengolahan Alat Light Traf Menggunakan Cell Surya Untuk Mencegah Serangga Pertanian Di Desa Bangkit Baru Barito Kuala - Arifin , Jainal; Herlina, Firda; Hartadi , Budi; Panca Asmara, Yuli (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
Bangkit Baru village is located in Barito Kuala, Mandastana sub-district, with a population of ± 1000 people, the majority of the people of Bangkit Baru village make their living as rice farmers, the area of ​​agricultural fields is up to 5,424 hectares, the size of the agricultural land in the village indicates that the majority of local people still depend on agricultural land. Rice is one of the staple foods of the Indonesian people. The development of an area means fertile agricultural land with agricultural products and plantations in the area which are useful for supplying food which is currently still declining. In this activity, the team carried out several methods, including field surveys, then continuing to look for problems that were hampering the local community and making tools to deal with pests and grasshoppers, as well as outreach to local residents. The use of this trap light tool is as a pest trap, the LED lights are included. The device will light up at night, the light will attract insect pests so they will fall into a container filled with water which is right under the UV lamp. Then, the water in the container will trap insects, this is a natural pest exterminator without using chemicals that are still used by local people.